A Risk Assessment Methodology for Toxic Chemicals Evaporation from Circular Pools - R Saravanan; T Karunanithi; L Govindarajan (Journal of Applied Sciences and Environmental Management, 2009)
This study presents a method for determining the mass transfer coefficient for the toxic chemicals evaporation from circular pools formed due to the failure of plant integrity or escape from valves. The approach used in this present research work is to develop a correlation by a robust optimization technique known as Genetic Algorithm from the experimental data. The developed correlation can be used to model the hydrocarbon evaporation from spills or releases at different wind speeds. From the mass transfer coefficient, the vapor concentration of the hydrocarbon spillage in the environment can be determined which can be used in quantitative risk analysis to predict the effect of toxic release.